STRATEGI KESANTUNAN BERBAHASA DI PENGADILAN (Penelitian Etnografi Komunikasi) - Masnunah Masnunah (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2018)
This study aimed to describe the language politeness strategy in the trial in the Special Class 1A District Court of Palembang which included positive and negative politeness strategies. This research is a qualitative research with ethnographic communication method. Data collection techniques and procedures used are observation, recording and transcripts. Data analysis is done by transcribing the recorded data into written form, then analyzed based on the problem formulation. Based on data analysis, language politeness in the trial is descriptively expressed through positive language politeness strategies including Notice strategy, attend to H, Intensify interest to H, Avoid disagreement, Presuppose / raise / assert, Joke, Assert or presuppose S's knowledge of and concern for H wants, Offer and promise, Include both S and H In the activity, and give (or ask for) reasons. Whereas through the negative language politeness strategy includes Be conventional conventional indirect, Be pessimistic, Minimize the imposition, give deference, Apologize, and State the FTA as a general rule that occurs naturally. The realization of the language politeness strategy that occurs shows that all speech participants in the trial understand their respective status and position so that the speeches delivered at the time of trial can maintain the face of each other's opponents when communication takes place. Keywords— Politeness Language Strategy, Court.